2013
DOI: 10.1089/hum.2012.219
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral Gene Transfer of Hepatic Stimulator Substance Confers Resistance Against Hepatic Ischemia–Reperfusion Injury by Improving Mitochondrial Function

Abstract: Hepatic stimulator substance (HSS) has been suggested to protect liver cells from various toxins. However, the precise role of HSS in hepatic ischemia-reperfusion (I/R) injury remains unknown. This study aims to elucidate whether overexpression of HSS could attenuate hepatic ischemia-reperfusion injury and its possible mechanisms. Both in vivo hepatic I/R injury in mice and in vitro hypoxia-reoxygenation (H/R) in a cell model were used to evaluate the effect of HSS protection after adenoviral gene transfer. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…More recently, the data confirmed that HSS plays the crucial function as an antioxidative agent sustaining the levels of reducing agents such as clusterin (38). A recent work in our laboratory demonstrated that HSS transfection decreases hypoxia and reoxygenation-induced mitochondrial ROS production and preserves mitochondrial respiratory chain complex activities (20). Hence, we propose that HSS might function as a free radical scavenger, thereby alleviating hepatic injury and promoting the survival of hepatocytes after HSS transfection.…”
Section: Discussionsupporting
confidence: 68%
“…More recently, the data confirmed that HSS plays the crucial function as an antioxidative agent sustaining the levels of reducing agents such as clusterin (38). A recent work in our laboratory demonstrated that HSS transfection decreases hypoxia and reoxygenation-induced mitochondrial ROS production and preserves mitochondrial respiratory chain complex activities (20). Hence, we propose that HSS might function as a free radical scavenger, thereby alleviating hepatic injury and promoting the survival of hepatocytes after HSS transfection.…”
Section: Discussionsupporting
confidence: 68%
“…Current research on mitochondrial involvement in I/R damage has focused mainly on the metabolic function rather than on mitochondrial dynamics and its mediated apoptosis, such as the reduction of adenosine triphosphate production, loss of mitochondrial membrane potential, reactive oxygen species generation, and cytochrome c release . However, the reason for these changes has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Nonlethal segmental (70%) hepatic warm ischemia was performed under 4% chloral hydrate anesthesia . An atraumatic clip was used to interrupt the arterial/portal venous blood supply to the cephalad liver lobes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations